Justiça seja feita: direito quilombola ao território - Lilian Cristina Bernardo Gomes (2009)
The joining forces of the local struggles of black communities of quilombos in Brazil and the Black Social Movements permitted, among a wide range of rights for people of African descent, the entry of the right of territorial communities for such communities in the 1988 Constitution, through art. 68 of ADCT. These communities had been invisible in the Brazilian public space since the Abolition of Slavery in 1888. However, their ways of creating, making, and living allowed the construction of ethnic territories with a plurality in the forms of cultural expression, ways of organizing production and uses of resources, which began to form themselves in a historical and cultural heritage of all the Brazilian population. The entry of this right into the pubic national scene points to the expansion of levels of social justice in Brazil. Social justice for these groups articulated a three angles dimension: the recognition of identities and rights, material and symbolic redistribution, and political and legal representation in the public space. However, the enforcement of this right is not a matter of easy implementation in Brazil due to the fact that it involves issues of land and race, two difficult issues addressed in the context of a supposed racial democracy, denounced as a way of seeing as natural the racial inequality especially by Black Social Movements since the 1940s. These complaints have become more striking after the 1970s, with the strengthening of civil society in Brazil. Since the colonial period, the Brazilian agrarian elite tended to concentrate land, creating the foundation for the development of a differentiated citizenship, which has distributed rights according to socioeconomic differences, such as property, income, occupation and access to formal education. This led to the development in Brazil, of different categories of citizens, increasing inequalities between owners and non-owners. The entry of this right in the national public scene, from the guarantee of the right of black communities of quilombos in the Constitution, created a public arena of contention that confirmed the interest of the landowning elite, organized in the Bancada Ruralista, a group with strong agenda power in Brazilian public space, especially in the legislative body. On the other hand, from the guarantee of that right came the Movement Quilombola that, despite the low power agenda, pluralizes the themes and demands in the Brazilian public arena. O presente trabalho concentra a atenção noimpacto desse Movimento Quilombola no espaço público e dos conflitos enfrentados pelas comunidades quilombolas ligados a diferentes atores sociais, econômicos e/ou estatais em torno do processo de titulação dos territórios quilombolas, em três estados brasileiros: Maranhão, Minas Gerais e Rio de Janeiro. This paper focuses attention on the impact of the Quilombola Movement in the public space and the conflicts faced by quilombola communities linked to different social actors, economic and / or state concerning the titling process of quilombolas territories in three Brazilian states: Maranhão, Minas Gerais and Rio de Janeiro. A partir do estudo de caso comparativo entre as três primeiras áreas tituladas em cada um desses estados (Frechal, Porto Coríse Campinho da Independência) e de três conflitos emblemáticos com a União (Alcântara, Mumbuca e Marambaia), procura-se indicar o que se apresenta no cenário desse direito como potencialidade para a efetivação da titulação dos territórios quilombolas e, como limite, o quemantém os desafios para o alcance da justiça social no Brasil para esses grupos. From the comparative case study among the first three areas with titles in each of those states (Frechal, Porto Corís Campinho da Independencia) and three emblematic conflicts with the Union (Alcântara, Mumbuca e Marambaia), we attempt to show in the background of this right the capability for effective titling the quilambolas territories, and, as a limit, what keeps the challenges for achievingsocial justice to these groups in Brazil.